KEUNGGULAN BERSAING: IMPLIKASI DARI SUPPLY CHAIN MANAGEMENT DAN KINERJA PERUSAHAAN - Barima, Hima (UNPERBA, 2023)
The development of a dynamic industry in the current global era become a trigger for many organizations Usaha Kecil Menengah (UKM) to explore the potential, as well as identifying the key success factor to excel in an increasingly competitive rivalry. One felt the most impact is in the textile industry. This relates to the competitiveness of the industry which is an important factor to be able to survive and become a winner in the competition. The business environment today is characterized by the development of technology that is faster, shorter product life cycles, and a more intense global competition. To be more responsive to customer needs and market requirements, the company should be more than the speed of delivery and quality products. It is also necessary integration in the supply chain. This study was conducted to investigate the effect of supply chain management in the company's performance and its application on competitive advantage. Questionnaires were sent to centers shirt Sacred Road Bandung and using 70 questionnaire as a measuring tool. Through a simple regression analysis and three hypotheses. The results showed that supply chain management has a significant impact on the company's performance and its application on competitive advantage.